Iraqi EFL University Students’ Level in Reading Comprehension - Muhammed, Ibtisam Jassim (Journal of Tikrit University for Humanities, 2024)
This study aims to find out the level of Iraqi EFL university students’ in reading comprehension through: Finding out Iraqi EFL university students’ level in reading comprehension. Finding out whether there are any significant differences between the achievement of the experimental group and that of the control group in the post-test. The following hypotheses have been posited to achieve the aims of the research. 1- The average level of the students’ achievement in the post-test within the theoretical mean scores of achievements in reading comprehension. 2.There are no statistically significant differences in the mean scores of the experimental group’s achievements and that of control group in the post-test. To verify the hypotheses of this study, a sample of sixty male and female students who represent 17% of its original population have been randomly selected from the second year of Basic Education collage in Mosul university .The sample is divided into two equal groups, i.e. the experimental and the control groups, both groups are equalized in their ages, parents’ academic attainment, and students’ scores in the pretest. An achievement test of twenty questions has been constructed, validated, and applied to the two groups . The collected data have been statistically analyzed and the main results are as follows: Iraqi EFL students` level in Reading Comprehension is within the average level. There are statistically significant differences in the mean scores of the experimental group’s achievements and that of control group in the post-test.